Otimização das condições de síntese e aplicação de agregados enzimáticos reticulados de β-galactosidase de Aspergillus oryzae com propriedades magnéticas - Ribeiro, Laiza Brito (2023)
The utilization of β-galactosidase on an industrial scale has been gaining prominence due to its application in various value-added processes, such as the production of galactooligosaccharides (GOS) and lactose hydrolysis for glucose and galactose production. However, the direct use of this free enzyme presents challenges for large-scale applications and processing. To overcome this issue, enzymatic immobilization methodologies can be employed to enhance the properties and applicability of the enzyme. In order to assure viability and advantage in the process, efficient, straightforward, and cost-effective immobilization techniques are looked after. Among these techniques, magnetic cross-linked enzyme aggregates (mCLEA) stand out as enzyme aggregates that do not require physical support, thereby reducing costs and improving productivity. This study aims to optimize the immobilization conditions of β-galactosidase from Aspergillus oryzae using the magnetic cross-linked enzyme aggregates (mCLEA) methodology, with the goal of producing an active and stable heterogeneous biocatalyst for lactose hydrolysis and lactulose production. An experimental design was conducted to assess the influence of pH (4 - 9), cross-linker concentration (dextran: 14 - 52 g • L-1), and cross-linking time (5 – 19 h), with the response variable defined as the biocatalyst's capacity to hydrolyze lactose. The optimized conditions were achieved at pH 7.38, dextran concentration of 32.05 g ∙ L-1, and cross-linking time of 14.88 h, resulting in 36.84 % lactose bioconversion to glucose and galactose after 7 h of reaction. The optimized dextran-based magnetic cross-linked enzyme aggregates (mCLEA-DEX-βGAL) of β-galactosidase from Aspergillus oryzae were also characterized for thermal stability (50°C and 60°C) and operational stability in lactose hydrolysis. The biocatalyst exhibited distinct behavior at 50°C (t 1/2 =7.6 h) and 60°C (t 1/2 = 22 min). At 60°C, the behavior of mCLEA-DEX resembled that of the free enzyme under this condition. The biocatalyst demonstrated favorable reusability, maintaining 59.72% of relative activity after 10 cycles. In terms of lactulose production, it was feasible to synthesize lactulose using lactose and fructose as substrates simultaneously, with the free enzyme achieving maximum production in 10 min (2.11 g∙L-1) and mCLEA-DEX in 5 min (1.72 g∙L-1). These findings indicate that heterogeneous biocatalysts hold promise for industrial applications, attributed to their enhanced thermal and operational stability. They can also be considered a promising, ecologically sustainable, and scalable alternative for lactulose synthesis.